Barley stripe mosaic virus cb protein targets thioredoxin h-type 1 to dampen salicylic acidmediated defenses - Jiang, Z.; Jin, X.; Yang, M.; Pi, Q.; Cao, Q.; Li, Z.; Li, D.
Salicylic acid (SA)acts as a signaling molecule to perceive and defend against pathogen infections. Accordingly, pathogens evolve versatile strategies to disrupt the SA-mediated signal transduction, and how plant viruses manipulate the SA-dependent defense responses requires further characterization. Here, we show that barley stripe mosaic virus (BSMV)infection activates the SA-mediated defense signaling pathway and upregulates the expression of Nicotiana benthamiana thioredoxin h-type 1 (NbTRXh1). The ?b protein interacts directly with NbTRXh1 in vivo and in vitro. The overexpression of NbTRXh1, but not a reductase-defective mutant, impedes BSMV infection, whereas low NbTRXh1 expression level results in increased viral accumulation. Similar with its orthologs in Arabidopsis (Arabidopsis thaliana), NbTRXh1 also plays an essential role in SA signaling transduction in N. benthamiana. To counteract NbTRXh1-mediated defenses, the BSMV ?b protein targets NbTRXh1 to dampen its reductase activity, thereby impairing downstream SA defense gene expression to optimize viral cell-to-cell movement. We also found that NbTRXh1-mediated resistance defends against lychnis ringspot virus, beet black scorch virus, and beet necrotic yellow vein virus. Taken together, our results reveal a role for the multifunctional ?b protein in counteracting plant defense responses and an expanded broad-spectrum antibiotic role of the SA signaling pathway.